Risk Factors for Hepatitis B in Sidomulyo Subdistrict, Samarinda City - Yasmine Naura Aurelya; Puspita Wulan; Siti Maysarah; Muhammad Rizky Aulia; Risva Risva (Universitas Mulawarman, 2026)
Hepatitis B is an infectious disease caused by the Hepatitis B virus (HBV) that can progress to liver cirrhosis and liver cancer if not properly managed. This study aimed to identify risk factors associated with Hepatitis B disease and their relationship with Hepatitis B vaccination history in the working area of Sidomulyo Primary Health Center, Samarinda Ilir District, Samarinda. A cross-sectional design with a rapid epidemiological survey approach was employed. Cluster sampling was used to recruit 210 respondents, and data were collected using a structured questionnaire. Univariate and bivariate analyses were performed using Chi-Square tests. The results showed that the majority of respondents were adults (97.1%), female (79.5%), had senior high school education (61.9%), and earned less than IDR 2 million per month (56.2%). A total of 75.7% had no history of Hepatitis B vaccination, and only 11.0% had received complete doses. Chi-Square analysis revealed significant associations between blood transfusion history (p=0.038), surgical history (p=0.007), and education level (p=0.004) with Hepatitis B vaccination history. No significant associations were found for sex, hemodialysis history, tattoo history, or sharing personal items. In conclusion, Hepatitis B vaccination coverage among adults remains very low. Community-based vaccination programs and intensive health education are urgently needed, particularly targeting low-education and low-income groups.